Розвиток навчального і науково-дослідного сектора інформаційного суспільства в Україні - Zgurovsky, M. Z. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The Grid-infrastructure for support of education and research in Ukraine is considered. Main components of this infrastructure are: Ukrainian Research and Academic Network, 128-processor cluster supercomputer, the system of distance learning, distributed information resources in education and science, electronic libraries and the administrative and educational system "Osvita". Grid-infrastructure provides the Ukrainian universities, research centers and virtual laboratories by the information and required computational resources. In conclusion an example of using the Ukrainian research and educational Grid-infrastructure for solving problems of ecological monitoring and telemedicine support for the Chernobyl nuclear power plant area was considered.